Corporate governance and sustainable prosperity - Lazonick, William; O'Sullivan, Mary. (Houndmills, Basingstoke, Hampshire ; New York : Palgrave, 2001)
Through historical analysis and comparisons with Germany and Japan, this book focuses on the microeconomics of corporate investment behaviour, and the macroeconomics of household saving behaviour in the US. It analyzes the factors which have influenced corporate investment since the 1980s.
Includes bibliographical references and index.
Keywords: Corporate governance; Occupations; Economic development